LINGKUNGAN PERSPEKTIF AL-QUR'AN: Kajian Ayat-Ayat al-Fasad Dengan Pendekatan Maqasid al-Shari'ah - Syaifudin; Mahmud, Ali (SAMAWAT: Journal Of Hadith and Qur'anic Studies, 2023)
The environment and humans are a series that are interrelated with each other, humans can even be understood as khalifah fil ard whose obligations are to protect and regulate this universe, not just to prioritize needs without thinking further about the impact fasad (environmental damage) resulting from every behavior. This article tries to examine how the verses are interpreted fasad (environmental damage). This research is library research which uses analytical descriptive methods. In this case, Islam has a scientific branch, to be precise Maqasid al-Shari'ah there is a term al-kulliyat al-khams (five main things) maqasid al-shari’ah as the existence of how efforts to keep from fasad (environmental damage). Environmental damage can be categorized in one way or another al-kulliyat al-khams, or the five main things namely in hifdzu al-mall (protecting wealth) which means that by protecting the environment the benefits obtained can be enjoyed by descendants or the next generation